After generative AI : preparing faculty to transform education, learning, and pedagogy - Aad, Samar S.; Hardey, Mariann (Emerald Publishing Limited, 2025)
In a landscape where technological advancements are disrupting and reshaping the educational paradigm, After Generative AI serves as a comprehensive guide to navigate the complexities and opportunities presented by Generative AI (GAI) and guide readers through strategies that must be implemented for a successful journey with GAI. From ChatGPT, to Bard, to CANVA, educators are seeking practical insights into how to harness the power of GAI effectively. After Generative AI provides a consolidated, accessible resource that caters to students and faculty, providing them with the knowledge and strategies to thrive in an AI-enhanced educational environment. Each chapter demystifies GAI for educators and learners alike, offering a clear and accessible explanation of the basics, applications, and implications of GAI in education. This is a foundational understanding for readers, ensuring they are equipped to make informed decisions about integrating GAI into their teaching and learning processes. Going beyond basic explanations, Hardey and Aad provide practical insights and implementation strategies that recognize the concerns and ethical challenges related to GAI, such as bias in algorithms, privacy issues, and the need for inclusivity. After Generative AI fills a crucial gap in the literature by providing a practical, insightful, and forward-looking guide to GAI in education. Through comprehensive coverage, real-world examples, and ethical considerations, educators will feel empowered and learners ready to embrace GAI's transformative potential while responsibly navigating its challenges.
Keywords: Educational innovations.; Artificial intelligence.; Education -- Computers & Technology.; Educational equipment and technology, computer-aided learning (CAL); elektronické knihy; electronic books